Pengembangan E-Learning Moodle Berbasis Virtual Private Server (VPS) Untuk Meningkatkan Hasil Belajar Pengetahuan Peserta Didik di Tengah Pandemi Covid-19 Pada Mata Pelajaran Geografi (Studi Kelas XI SMA Negeri 1 Teras Boyolali Tahun Ajaran 2020/2021) - Rizca Nurul Istiqomah Permata Indah; Djoko Subandriyo; Singgih Prihadi (GEADIDAKTIKA, 2022)
The research aims to: (1) to determine the feasibility of e-learning moodle based on Virtual Private Server to improve student learning outcomes; (2) determine the effectiveness of e-learning moodle based on Virtual Private Server to improve student learning outcomes; (3) to determine the effect of e-learning moodle on learning outcomes in the knowledge section of students. The method used in this research is research and development. The research subjects were theory experts, media experts, teachers, and students in class XI IPS 1,2, and 4. The data collection instruments used theory expert validation sheets, media expert validation sheets, teacher assessment sheets, student assessment sheets, and tests and documentation.The results of this study are: (1) e-learning moodle based on Virtyal Private Server is declared feasible based on theory expert judgment, teacher assessment, and student assessment by getting a score mode of 5 (excellent category on a Likert scale), as well as an assessment from media experts with score mode 4 (good category in Likert Scale); (2) e-learning Moodle based on Virtual Private Server is more effective in improving the learning outcomes of students' knowledge based on the higher class average on the cognitive pretest and posttest results that is 55.45 to 88.36 compared to MS Teams media where the class mean pretest results and cognitive posttest that is 53.56 to 76.88; (3) e-learning moodle based on Virtual Private Server has a significant effect on the learning outcomes of students’ knowledge with a Sig (2-tailed) value of 0.000 where 0.000 <0.05 so that there is a significant difference in the average towards student learning outcomes for the pretest and posttest scores in the experimental class. Keywords: Media Development, Virtual Private Server-based Moodle E-Learning, Learning Outcomes of Students' Knowledge